TARIYXÍY-MÁDENIY MIYRAS OBYEKTLERINIŃ TURIZMDI RAWAJLANDÍRÍWDAǴÍ ORNÍ - Najimova, F.M. (SCIENCE and SOCIETY, 2025)
This article describes the protection of Karakalpakstan’s historical and cultural heritage sites, regulatory and legal documents, and the work being done to develop international, domestic, and pilgrimage tourism in Uzbekistan.